1993
DOI: 10.1079/bjn19930109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute and chronic level of protein supply on metabolic leucine utilization in growing and mature rats

Abstract: Effects of acute (meal) and chronic (diet) level of protein supply on metabolic leucine utilization were investigated in growing (10 weeks) and mature (> 1 year) rats. Rats were conditioned on a high-protein (HP) diet (210 g casein/kg feed) or a low-protein (LP) diet (75 g casein/kg feed) from 7 weeks of age.Overnight-fasted rats were offered a HP or LP meal during a 8 h I4CO2 breath test with a constant infusion of either L-[ l-14C]leucine (carboxyl, CL) or ~-[U-'~Cjleucine (universal, UL). Before the meal 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The recovery of label in breath air of 1‐ 13 C 1 ‐leucine injected lactating mink ( Mustela vison ) was significantly depressed when dietary protein concentration was decreased (Tauson et al., 2001). Weijs et al. (1993) also demonstrated that the 14 CO 2 output was higher in l [1‐ 14 C]leucine‐injected rats fed acutely or chronically with a HP diet compared with those provided with a LP diet.…”
Section: Resultsmentioning
confidence: 85%
“…The recovery of label in breath air of 1‐ 13 C 1 ‐leucine injected lactating mink ( Mustela vison ) was significantly depressed when dietary protein concentration was decreased (Tauson et al., 2001). Weijs et al. (1993) also demonstrated that the 14 CO 2 output was higher in l [1‐ 14 C]leucine‐injected rats fed acutely or chronically with a HP diet compared with those provided with a LP diet.…”
Section: Resultsmentioning
confidence: 85%
“…Although pregnancy is an interesting physiological phenomenon in itself, the primary objective of the present study was to check whether growth during pregnancy had comparable effects on leucine utilization as growth during development. In an earlier study with male rats, growth significantly improved leucine utilization in the fasted state as well as after feeding (Weijs et al 1993). The method used in the present study is identical to that used in the previous study, which is discussed below.…”
Section: Discussionmentioning
confidence: 69%
“…In the present study it was intended to investigate the qualitative effect of pregnancy on the efficiency of leucine utilization during fasting and feeding. For this study the simplest approach was adopted, which had been shown previously to be valuable (Weijs et al 1993). The fate of leucine was traced with [14C]leucine, and the oxidized part was measured continuously.…”
Section: On the Methodsmentioning
confidence: 99%